A global geography of synchrony for marine phytoplankton. Issue 8 (29th May 2017) - Defriez, Emma J.; Reuman, Daniel C.
Abstract: Aim: Spatial synchrony in plankton is imperfectly understood yet may have far‐reaching implications, for example for carbon export to the deep ocean. Several techniques have been used to describe patterns of spatial synchrony, from correlation coefficients to spectral methods. Some studies have used temporally extensive data sets to identify causes of synchrony. This study instead uses the exceptional spatial extent provided by remotely sensed data to describe, for the first time as far as we know, geographical patterns of synchrony in marine phytoplankton. We use these patterns to illuminate drivers of synchrony and of its geography. Location: The oceans. Time period: 2003–2015. Major taxon: Chlorophyll a ‐containing phytoplankton. Methods: Synchrony in chlorophyll a concentrations is mapped globally. Spatial statistics and model selection are used to illuminate main statistical determinants of synchrony and of geographical patterns in synchrony. Results: The first main result is that there is a pronounced and previously unmapped geography of synchrony for phytoplankton. For instance, synchrony was highest in the open ocean, specifically in gyres, and lowest in coastal regions. Spatial modelling provided the second main result that synchrony in sea surface temperature (SST) was a major statistical determinant of chlorophyll synchrony in both the Pacific and Atlantic Oceans, indicating a strong Moran effect, although possibly an indirect and/or complex one. In the Pacific Ocean, this effect depended on the time‐scales on which synchrony was assessed, providing our third result, which is that synchrony of phytoplankton and its geography can be time‐scale specific. Synchrony of surface solar irradiance was not associated with synchrony of chlorophyll. Main conclusions: To our knowledge, this study is the first to map geography of synchrony in marine plankton. We showed that this geography is pronounced. Geographical patterns illuminated determinants of synchrony. The geography of synchrony is a major phenomenon that has been little explored.